Pengaruh Smartphone Terhadap Anak Usia Dini - Noor Muhammad Ghofururrohim; Raka Nur Wicaksono; Andhita Risko Faristiana (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
This article aims to find out the development of smartphones and the resulting impact. The definition of a smartphone is a small electronic device that has various functions and the latest technology, which makes human life more practical. In the context of early childhood development, the use of smartphones has an influence on their development. Technology can be an effective learning medium and can increase children's creativity, but it must be balanced with interaction with the surrounding environment. Research shows that smartphone use can have a negative impact on early childhood social development. Excessive use can cause children to become introverted, experience sleep disturbances, tend to be alone, show violent behavior, inhibit creativity, and increase the risk of cyberbullying. To overcome this problem, the solution is to limit the use of smartphones, supervise children while using smartphones, and involve themselves as parental figures who play an active role. Providing an appropriate time schedule for children to use smartphones is also important, so that smartphone use does not hinder early childhood social development. The role of parents in this case is very important to provide appropriate supervision and direction. By taking these steps, it is hoped that the negative effects of smartphone use can be minimized, while early childhood social development is well maintained.